2012
DOI: 10.1007/s10565-012-9236-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress reaction of kidney epithelial cells to inorganic solid-core nanoparticles

Abstract: A route of accumulation and elimination of therapeutic engineered nanoparticles (NPs) may be the kidney. Therefore, the interactions of different solid-core inorganic NPs (titanium-, silica-, and iron oxide-based NPs) were studied in vitro with the MDCK and LLC-PK epithelial cells as representative cells of the renal epithelia. Following cell exposure to the NPs, observations include cytotoxicity for oleic acid-coated iron oxide NPs, the production of reactive oxygen species for titanium dioxide NPs, and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…The internalization of NPs is highly sizedependent; however, uptake might not follow commonly defined size limits, and kinetics of uptake for the same type of NPs varies in the different cell types (dos Santos et al, 2011). NP transport is most affected by tightness of the cell barrier, with transport increasing in the order: brain5placenta5kidney after 2 h and brain5kidney5placenta after 24 h exposure as shown from transport studies of OC-Fe 3 O 4 NPs utilising different cell types (Figure 1; Correia Carreira et al, 2015;Halamoda Kenzaoui et al, 2012a, 2013b. The different order in extent of transport with time is likely to be due to changes in cell growth in each model and will reflect differences in the tightness of the barrier formed.…”
Section: Bioavailability Of Nanomaterial: Uptake Subcellular Localizmentioning
confidence: 99%
See 1 more Smart Citation
“…The internalization of NPs is highly sizedependent; however, uptake might not follow commonly defined size limits, and kinetics of uptake for the same type of NPs varies in the different cell types (dos Santos et al, 2011). NP transport is most affected by tightness of the cell barrier, with transport increasing in the order: brain5placenta5kidney after 2 h and brain5kidney5placenta after 24 h exposure as shown from transport studies of OC-Fe 3 O 4 NPs utilising different cell types (Figure 1; Correia Carreira et al, 2015;Halamoda Kenzaoui et al, 2012a, 2013b. The different order in extent of transport with time is likely to be due to changes in cell growth in each model and will reflect differences in the tightness of the barrier formed.…”
Section: Bioavailability Of Nanomaterial: Uptake Subcellular Localizmentioning
confidence: 99%
“…In vitro experiments with cells representing different organ targets revealed that oxidative stress and toxic effects induced by NPs depend on the NPs' properties, the test used and the cell type. Polylactic-coglycolic acid (PLGA-PEO) NPs induced little or no oxidative stress in any cell type compared with solid-core metallic NPs which generally produced ROS (Guadagnini et al, 2015b;Halamoda Kenzaoui et al, 2012c, 2013b. Genotoxicity induced by NPs depends on the NPs, the dispersion protocol and the measured endpoint (Magdolenova et al, 2012a).…”
Section: Testing Strategymentioning
confidence: 99%
“…For cell viability and DNA synthesis, cells were grown in 48-well cell culture plates (Costar, Corning, NY, USA) until 75% confluent and exposed to the USPIO NPs in complete culture medium for the concentration and time indicated, then washed in saline (0.9% NaCl (w/v)). Cell viability was evaluated using the MTT assay, essentially as previously described . DNA synthesis was determined by tritiated thymidine ( 3 H-T) incorporation, essentially as previously described .…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Cells were grown in 48-well plates until 75% confluent, then exposed to the USPIO NPs for the concentration and time indicated. Then, cell-associated iron content was quantified by the soluble Prussian Blue reaction, essentially as previously described . Briefly, for quantitative iron determination, the cell layers were dissolved in 6 N HCl, then a 5% solution of K 4 [Fe(CN) 6 ]·3H 2 O (Merck, VWR international, Nyon, Switzerland) in H 2 O was added for 10 min and the absorbance was measured at 690 nm in a multiwell plate reader (iEMS Labsystems).…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation